Effects of fractional dose yellow fever vaccination: a systematic review and meta-analysis - Nnaji, Chukwudi Arnest (Department of Public Health and Family Medicine, 2019)
Persistent yellow fever endemicity and continued outbreaks have continued to increase vaccine demand, while straining global vaccine supply. Fractional dose vaccination is being considered as a dose-sparing strategy to mitigate current global vaccine shortages. This study therefore assessed the effects of fractional dose yellow fever vaccination, in comparison to those of the standard dose. We registered the review in the prospective register of systematic reviews; conducted a comprehensive search of published and grey literature; used standard Cochrane methods to collect and synthesise the evidence and followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidance. We stratified analyses by the strength of the fractional dose. We retrieved 2495 records from the literature search, nine of them potentially eligible. We included six eligible studies (three randomised and three quasi-randomised trials), with 2371 participants. There was no statistically significant difference in immunogenicity between participants who received fractional doses containing one-third (two trials, 547 participants: RR 1.02, 95% CI 1.00 to 1.04; I2 = 0%), 1/5th (one trial, 155 participants: RR 1.00, 95% CI 0.98 to 1.03), 1/10th (four trials, 890 participants: RR 0.99, 95% CI 0.96 to 1.01, I 2 = 0%), and 1/50th (three trials, 661 participants: RR 0.97, 95% CI 0.92 to 1.02, I2 = 72%) of the standard dose and those who received the full standard dose. However, immunogenicity was significantly lower among participants who received fractional doses containing 1/100th (four trials, 868 participants: RR 0.92, 95% CI 0.87 to 0.97, I2 = 60%) and < 1/100th (five trials, 1053 participants; RR 0.53, 95% CI 0.44 to 0.64, I2= 98%) of the standard dose compared to participants who received the full standard dose. Minor adverse events following vaccination did not differ across doses, but no serious adverse events were reported in any study arm. The combined data provide moderate certainty evidence that there is little or no difference in immunogenicity between ≥1/50th fractional doses and the standard dose of yellow fever vaccines. However, these studies were of short duration ranging from four weeks to a year. These findings support the use of fractional dose vaccination as a dose-sparing strategy for yellow fever vaccination.